Epileptic spikes in Rasmussen's encephalitis: Migratory pattern and short-term evolution. A MEG study. Issue 10 (October 2017) - Rossi Sebastiano, Davide; Visani, Elisa; Duran, Dunja; Freri, Elena; Panzica, Ferruccio; Chiapparini, Luisa; Ragona, Francesca; Granata, Tiziana; Franceschetti, Silvana
Highlights: MEG can reveal multifocal epileptic activity with different patterns in Rasmussen's Encephalitis (RE) patients. The multifocal interictal epileptic activity in RE may change over time. In RE, the cortical areas most involved in epileptogenesis often do not match the most atrophic ones. Abstract: Objective: We aimed this study at identifying cortical areas involved in the generation of interictal spikes in Rasmussen's Encephalitis (RE) patients using magnetoencephalography (MEG), at comparing spike localization with the degree of cortical atrophy detected by MRI, and at identifying short-term changes during the follow-up. Methods: Five patients with RE underwent two MEG and magnetic resonance imaging (MRI) (six months interval). The sources of visually detected spikes were estimated using equivalent current dipoles technique; these were then superimposed on individual MRI and clustered; the locations of the clusters were related to the MRI stage of cortical atrophy. Results: All patients showed spikes and clusters located in different cortical areas in both recordings; the locations had a limited correspondence with cortical atrophy. The second recordings showed changes in the localisation of spikes and clusters, and confirmed the dissimilarities with neuroradiological abnormalities. Conclusions: The presence of clusters of spikes of variable localisation suggests that RE progresses in a multifocal and fluctuating manner. The cortical areas most involved in epileptogenesis did not completely coincide with the most atrophic areas. Significance: MEG can contribute to evaluating multifocal hemispheric spikes in RE and to better understand the time course of epileptogenic process.